2020
DOI: 10.25300/misq/2020/15610
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of IT Users’ Coping Strategies: Uncovering Momentary Emotional Load, Routes, and Sequences

Abstract: Despite the positive aspects of information technology (IT) use, it is common for users to experience negative IT incidents. Examples of negative IT incidents include getting lost in an unfamiliar country due to a dysfunctional map application and missing a monetary insurance benefit due to the failure of an activity tracker application. Such incidents can harm IT providers by giving rise to user dissatisfaction, discontinued use, switching, and negative word-of-mouth. To minimize this harm, it is important to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…Through the significant mediating impact of digital transformation as transformational logic, our study confirmed the H3c. On the one hand, our findings enriched the institutional perspective of social enterprise legitimacy by adding new interpretations (Salo et al , 2020). We have supplemented and interpreted the digital transformation literature on how digital technology can influence the legitimacy of hybrid organizations (Fitzgerald et al , 2014; Annarelli et al , 2021).…”
Section: Data Analysis and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Through the significant mediating impact of digital transformation as transformational logic, our study confirmed the H3c. On the one hand, our findings enriched the institutional perspective of social enterprise legitimacy by adding new interpretations (Salo et al , 2020). We have supplemented and interpreted the digital transformation literature on how digital technology can influence the legitimacy of hybrid organizations (Fitzgerald et al , 2014; Annarelli et al , 2021).…”
Section: Data Analysis and Discussionsupporting
confidence: 57%
“…However, there is a core premise assumption of related studies that cognitive legitimacy can only obtain through an established approach (Chell et al , 2010; Dart, 2004), where digital transformation has not been considered as the transformation logic and integrated into the theoretical framework from the institutional perspective (Salo et al , 2020). Especially in confront new challenges from a post-pandemic context, it is difficult for social enterprises to amplify company impact only by following an established approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, we chose to employ the literature on IT affordances and self-regulation in place of other potentially relevant literature. For example, we acknowledge that the literature on coping with IT (e.g., Beaudry and Pinsonneault 2005;Salo et al 2020;) could offer insights into technostress mitigation, especially on emotions. However, we estimated the IT affordance literature would be more precise in focusing on the IT and user components simultaneously and the self-regulation literature would better extract the main components needed for changing one's use practices.…”
Section: Limitationsmentioning
confidence: 99%
“…The training is considered an effective stress coping strategy (Skinner et al, 2003;Salo et al, 2020). Training instills the capability to handle the challenges arising out of work.…”
Section: Training (As a Moderator) And Employee Performancementioning
confidence: 99%